2005
DOI: 10.1042/bj20041995
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenation by COX-2 (cyclo-oxygenase-2) of 3-HETE (3-hydroxyeicosatetraenoic acid), a fungal mimetic of arachidonic acid, produces a cascade of novel bioactive 3-hydroxyeicosanoids

Abstract: Cyclo-oxygenases-1/2 (COX-1/2) catalyse the oxygenation of AA (arachidonic acid) and related polyunsaturated fatty acids to endoperoxide precursors of prostanoids. COX-1 is referred to as a constitutive enzyme involved in haemostasis, whereas COX-2 is an inducible enzyme expressed in inflammatory diseases and cancer. The fungus Dipodascopsis uninucleata has been shown by us to convert exogenous AA into 3(R)-HETE [3(R)-hydroxy-5Z,8Z,11Z,14Z-eicosatetraenoic acid]. 3R-HETE is stereochemically identical with AA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 51 publications
0
35
0
Order By: Relevance
“…Here, arachidonic acid (AA) is released from the infected or inflamed host tissue /cell and then converted by Candida albicans to 3R-hydroxy eicosatetraenoic acid (3R-HETE), which serves as substrate for COX-2 in host tissue /cell to produce proinflammatory 3-OH-PGE 2 . Strikingly, in this investigation a cascade of novel bioactive 3-OH eicosanoids, produced from 3R-HETE via mammalian COX-2, was uncovered 5 . In addition, it was found that C. albicans selectively upregulates COX-2 in mammalian cells 7 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, arachidonic acid (AA) is released from the infected or inflamed host tissue /cell and then converted by Candida albicans to 3R-hydroxy eicosatetraenoic acid (3R-HETE), which serves as substrate for COX-2 in host tissue /cell to produce proinflammatory 3-OH-PGE 2 . Strikingly, in this investigation a cascade of novel bioactive 3-OH eicosanoids, produced from 3R-HETE via mammalian COX-2, was uncovered 5 . In addition, it was found that C. albicans selectively upregulates COX-2 in mammalian cells 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The PGs are produced by aspirinsensitive enzymes i.e. cyclooxygenase 1 (COX-1, a constitutive enzyme involved in hemostasis) and cyclooxygenase 2 (COX-2, an inducible enzyme expressed in inflammatory diseases and cancer) 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it will be necessary to assess if the conversion of anandamide into 3-HAEA does occur also during candidiasis, and, if so, to what extent. The production of 3-hydroxyeicosanoids like 3-hydroxyPGE 2 upon infection of HeLa cells with C. albicans supports the hypothesis that also 3-HAEA might be formed during infection with this pathogenic fungus (23). On the other hand, still enough endogenous anandamide to activate CB 1 and CB 2 receptors might remain even if this conversion were to occur in vivo, and this would counteract the effects of 3-HAEA.…”
Section: Discussionmentioning
confidence: 57%
“…Thus, Candida can chemically modify the metabolites of the host cell to facilitate infection. Notwithstanding the presence of a C-3 hydroxyl, 3(R)-HETE is a substrate of cyclooxygenase-2 (an enzyme up-regulated during candidiasis), thereby generating compounds that, like 3(R)-hydroxy-PGE 2 , are capable to induce interleukin-6 gene expression via the EP 3 receptor (22,23), and to ultimately trigger further inflammation cascades.…”
mentioning
confidence: 99%